Analisis Promotion Mix Terhadap Pemasaran Layanan Kontruksi Pada PT Khafi Multi Perkasa - Muhammad Agung Nugraha; Sri Sudiarti (MES Management Journal, 2023)
This study aims to determine the results of the analysis of the promotion mix on the marketing of goods and services as well as the forms of construction services that exist at PT. Khafi Multi Mighty. The type of method in this research is a qualitative type with a descriptive approach that is directed to be explained in greater detail about the actual situation that occurs in the field. This study also conducted direct interviews addressed to the Director of the company PT. Khafi Multi Mighty. This study shows the results that the promotion mix has not been implemented by employees so that it does not have a significant effect on service marketing, this is evidenced by their marketing method which only uses three components contained in the promotion mix. So that the services offered have not yet reached the desired point of satisfaction because the marketing system that is being implemented is not perfect. Keywords: Service Quality, Promotion Mix